Impact on disease-free survival of adjuvant erlotinib or gefitinib in patients with resected lung adenocarcinomas that harbor epidermal growth factor receptor (EGFR) mutations - Janjigian, Yelena Y. (2011)
BACKGROUND: Patients with stage IV lung adenocarcinoma and EGFR mutation derive clinical benefit from treatment with EGFR tyrosine kinase inhibitors (TKI). Whether treatment with TKI improves outcomes in patients with resected lung adenocarcinoma and EGFR mutation is unknown. METHODS: Data were analyzed from a surgical database of patients with resected lung adenocarcinoma harboring EGFR exon 19 or 21 mutations. In a multivariate analysis, we evaluated the impact of treatment with adjuvant TKI. RESULTS: The cohort consists of 167 patients with completely resected stage I–III lung adenocarcinoma. 93 patients (56%) had exon 19 del, 74 patients (44%) had exon 21 mutations, 56 patients (33%) received perioperative TKI. In a multivariate analysis controlling for sex, stage, type of surgery and adjuvant platinum chemotherapy, the 2-year DFS was 89% for patients treated with adjuvant TKI compared with 72% in control group (hazard ratio [HR] = 0.53; 95% confidence interval [CI] 0.28 to 1.03; p = 0.06). The 2-year OS was 96% with adjuvant EGFR TKI and 90% in the group that did not receive TKI (HR 0.62; 95% CI 0.26 to 1.51; p = 0.296). CONCLUSIONS: Compared to patients who did not receive adjuvant TKI, we observed a trend toward improvement in disease free survival among individuals with resected stages I–III lung adenocarcinomas harboring mutations in EGFR exons 19 or 21 who received these agents as adjuvant therapy. Based on these data, 320 patients are needed for a randomized trial to prospectively validate this DFS benefit.